Logistics and Supply Chain Performance Measurement: Comparison of Thai Government’s Practice to Theoretical Literature and Practical Case Studies - Chuchuai, Punyawan (2016)
Logistics and supply chain management are known as an essential part of current days’ business. Well-managed of them would bring a great result to business in this competitive and dynamic market. In order to improve the performance of overall Thailand’s industries, Thai government roles in supporting and promoting in scope of Logistics Office within the Department of Primary Industries and Mines are taking into account. This study will be examined Thai performance measurements and compared against theoretical indicators and actual case studies. It appears that the significant factors found in practical case studies are divided into two categories, relationship with customer such as reliability, flexibility, responsiveness, lead-time, and quality, and internal production process such as cost, manufactured related, communication, innovation, and employee related. By comparing those elements and theoretical measures with Thailand’s performance measurement, it can be concluded that there are some key factors that can be considered adding to Thai’s measure for further improvement, especially employee management and learning and growth aspect. However, there still has to be the evaluation on whether those indicators suit Thailand’s industrial environment, which could be the recommendation for future study.